Barsine deliciosa, a new species from China (Lepidoptera, Erebidae, Arctiinae) - Volynkin, Anton V.; Černý, Karel (Zootaxa, 2016)
A new Lithosiini species, Barsine deliciosa Volynkin & Černý, sp. n. is described from North China, Shanxi and Shaanxi provinces. A diagnostic comparison is made with Barsine flammealis Moore, 1878, Barsine linga Moore, 1859, Barsine delicia Swinhoe, 1891, Barsine conicornutata (Holloway, 1982), Barsine lucibilis Swinhoe, 1892 and Barsine striata (Bremer et Grey, 1852). Adults, male and female genitalia of the new, related and externally close species are illustrated.